2005
DOI: 10.1090/s0002-9939-05-07930-x
|View full text |Cite
|
Sign up to set email alerts
|

A remark on the homomorphism on 𝐶(𝑋)

Abstract: Abstract. Let X be a real compact space. Without using the axiom of choice we present a simple and direct proof that a non-zero homomorphism on C(X) is determined by a point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Later, Shirota [52] showed that X is realcompact if and only if to each algebra homomorphism ϕ from C (X) onto the real field R there corresponds a point x of X such that ϕ (f ) = f (x) for all f ∈ C (X). This remarkable necessary and sufficient condition for a Tychonoff space to be realcompact was obtained very recently by Ercan and Önal [26] via an elementary approach. These observations will be used next to obtain an alternative characterization of realcompact spaces which is a little more fit for our study.…”
Section: Concrete Situationsmentioning
confidence: 74%
“…Later, Shirota [52] showed that X is realcompact if and only if to each algebra homomorphism ϕ from C (X) onto the real field R there corresponds a point x of X such that ϕ (f ) = f (x) for all f ∈ C (X). This remarkable necessary and sufficient condition for a Tychonoff space to be realcompact was obtained very recently by Ercan and Önal [26] via an elementary approach. These observations will be used next to obtain an alternative characterization of realcompact spaces which is a little more fit for our study.…”
Section: Concrete Situationsmentioning
confidence: 74%
“…It should be pointed out that the idea of using projections in such a context is essentially due do to Aron‐Fricke in and Ercan‐Onal in .…”
Section: Realcompact Functionsmentioning
confidence: 99%
“…Proof of Theorem 1.1. In the proof we mainly follow the arguments of [3], so to be as self contained as possible, we repeat some parts of the proof therein. As indicated in [1], the implications (i) =⇒ (ii) and (ii) =⇒ (iii) are obvious.…”
Section: Proof Of Theorem 11mentioning
confidence: 99%